PENERAPAN METODE CCME-WQI UNTUK MENGANALISIS KUALITAS AIR DANAU DI PESISIR KAMPUNG YOBEH DISTRIK SENTANI KABUPATEN JAYAPURA - Suhartawan, Bambang -; Daawia, Daawia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2024)
This research aims to analyze the water quality of lakes on the coast of Kampung Yobeh, Sentani District, Jayapura Regency using the Canadian Council of Ministers of the Environment Water Quality Index (CCME-WQI) method. The analysis was carried out using eight water quality parameters which were compared with clean water quality standards in accordance with Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management (Appendix VI, Class 1). Sampling was carried out temporally in January, May and September 2024 to understand variations in water quality over different time periods. The research results show that the CCME-WQI value obtained is 24.177, which is included in the